2018
DOI: 10.18632/oncotarget.26123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic analyses guided by high resolution whole-genome SNP array reveals a possible role of CHEK2 in Wilms tumour susceptibility

Abstract: Wilms tumour (WT), the most frequent malignant childhood renal tumour, shows a high degree of genetic and epigenetic heterogeneity. Loss of imprinting on chromosome 11p15 is found in a large fraction of cases and mutations in a few genes, including WT1, CTNNB1, WTX, TP53 and, more recently, SIX1, SIX2 and micro RNA processing genes (miRNAPGs), have been observed. However, these alterations are not sufficient to describe the entire spectrum of genetic defects underlying WT development. We inspected data obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In conclusion, WT is a heterogeneous cancer (20), in which epigenetic alterations influence its biologic behavior. In this study, several miRNAs were found to be differentially expressed between non-neoplastic kidney tissue and WT tissue, and these differences were especially pronounced in DAWT and metastatic tumor tissues.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In conclusion, WT is a heterogeneous cancer (20), in which epigenetic alterations influence its biologic behavior. In this study, several miRNAs were found to be differentially expressed between non-neoplastic kidney tissue and WT tissue, and these differences were especially pronounced in DAWT and metastatic tumor tissues.…”
Section: Discussionmentioning
confidence: 94%
“…Wilms tumor presents a high degree of genetic and epigenetic heterogeneity. Although structural alterations in numerous genes have been associated with WTs, several cases have been identified where no mutations are present, suggesting that other mechanisms may be involved in WT etiology (20). MiRNAs are known to play roles in the epigenetic mechanisms involved in tumor development and are involved in numerous cellular pathways through their interactions with a wide variety of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, Gadd and colleagues identified germline CHEK2 variants in 3/117 (2.6%) and 8/651 (1.2%) patients with Wilms tumors in their discovery and validation sets, respectively [ 220 ]. Another report by Ciceri et al [ 221 ] found five carriers of rare missense or splicing CHEK2 variants among 96 Wilms tumor patients from Italy. While evidence of the association of CHEK2 germline mutations with an increased RCC risk is currently mounting, larger case control studies in RCC patients are required to confirm and refine the magnitude of the associated risk.…”
Section: Germline Chek2 Variantsmentioning
confidence: 99%
“…MYCN amplification enhances promoted the development of Wilms tumor through multiple mechanisms [9]. Moreover, numerous gene polymorphisms have been found to predispose to Wilms tumor [10][11][12], including WTX [13], P53 [14], CTNNB1 [15], BARD1 [16], HACE1 [17], LIN28B [18], XPD [19], hOGG1 and FEN1 gene [20], KRAS [21]. Although quite a few of predisposing genetic factors have been found, they are far from enough to explicitly explain the genetic pathogenesis of Wilms tumor.…”
Section: Introductionmentioning
confidence: 99%